A method for treating inclusions in modified steel using rare earth cerium during refining
By using rare earth cerium to treat inclusions in modified steel during steelmaking refining, the problem of low yield in calcium treatment is solved, high yield and stable inclusion modification effect is achieved, and the performance of steel is improved.
Patent Information
- Application Number
- CN202310612041.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-26
- Publication Date
- 2025-09-02
- Estimated Expiration
- 2043-05-26
AI Technical Summary
In the current steelmaking refining, calcium feeding is empirically empirically and has low yield, resulting in unstable inclusion modification effect and affecting steel performance.
The method of treating inclusions in modified steel using rare earth cerium, including converter or electric furnace smelting, aluminum deoxygenation, LF furnace or LF furnace → RH furnace refining, and continuous casting after refining. By controlling the addition time and amount of white slag composition and rare earth cerium, the yield and modification effect of rare earth cerium are ensured.
The yield of rare earth cerium is improved to 30-50%, so that the spherical rate of inclusions reaches more than 90%, the corrosion rate of steel is reduced, and the inclusion modification effect is stabilized.
Smart Images

Figure CN117089668B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of iron and steel metallurgy, and in particular relates to a method for treating inclusions in modified steel by using rare earth cerium during refining. Background Art
[0002] Common stable inclusions such as MnS and Al2O3 in steel can cause pitting corrosion and reduce fatigue life, thereby reducing the application of steel. Currently, calcium treatment is commonly performed during steelmaking and refining. Calcium treatment is the most common, direct, and effective method for modifying non-metallic inclusions in steel. After calcium treatment, Al2O3 forms low-melting calcium aluminate inclusions, and MnS is transformed into a single, uniform, spherical CaS inclusion, thereby reducing the impact of Al2O3 and MnS inclusions on steel properties. However, due to the chemically active nature and low boiling point of calcium metal itself, Ca will volatilize as Ca vapor under smelting conditions. This leads to the empirical use of calcium feeding during calcium treatment during steelmaking and refining, large fluctuations in calcium alloy yield, and a low yield of approximately 5-15%. This makes the modified inclusion effect unstable. Therefore, how to improve the effectiveness of inclusion modification during refining has become a difficult problem for the industry. Summary of the Invention
[0003] In view of the above analysis, in order to address the difficulties in the prior art, the present invention aims to provide a method for treating inclusions in modified steel using rare earth cerium during refining, so as to solve one of the technical problems in the existing steelmaking and refining calcium treatment, namely, the empirical calcium feeding amount, large fluctuations in calcium alloy yield, low yield, and unstable effect of modified inclusions.
[0004] The purpose of the present invention is mainly achieved through the following technical solutions:
[0005] The present invention provides a method for treating inclusions in modified steel using rare earth cerium during refining, comprising the following steps:
[0006] Step S1, converter or electric furnace smelting;
[0007] Step S2: When tapping steel from the converter or electric furnace, aluminum deoxidation and alloying operations are performed in the ladle;
[0008] Step S3, LF furnace or LF furnace → RH furnace refining, rare earth cerium treatment is performed in the last step of refining;
[0009] Step S4: continuous casting or die casting after refining.
[0010] Furthermore, in step S1, the steel type to be smelted is a steel type that usually requires calcium treatment during refining.
[0011] Furthermore, the steel types include pipeline steel, titanium-containing stainless steel, gear steel, heavy rail steel, electrical steel, non-quenched and tempered steel, deep drawing steel, structural steel, corrosion-resistant steel, wear-resistant steel, and 10# high-quality carbon steel.
[0012] Furthermore, in step 2, aluminum deoxidation is performed using aluminum blocks or aluminum particles, the purity of the aluminum blocks or aluminum particles reaches more than 99%, and the equivalent diameter is not greater than 12 mm.
[0013] Furthermore, in step 3, during the white slag operation in the LF furnace refining, the slag thickness is controlled to be 130-150 mm, the white slag duration is greater than 20 min, and argon is soft-blown before leaving the station.
[0014] Furthermore, the components of the white slag are, in mass percentage, CaO: 55-65%, SiO2: 5-8%, MgO: 11-15%, Al2O3: 15-24%, FeO+MnO<0.5%, and CaO / SiO2: 8.0-11.
[0015] Furthermore, in step 3, before rare earth cerium treatment, the mass percentage of Alt in the steel is controlled to be 0.02%≤Alt<1.00%, the mass percentage of total oxygen TO is below 0.01%, and the mass percentage of sulfur S is below 0.05%.
[0016] Furthermore, in step 3, rare earth Ce treatment is performed in the last step of refining: when only LF furnace refining is performed, rare earth cerium is added 4 minutes before leaving the station; when refining from LF furnace to RH furnace, rare earth cerium is added 4 minutes before breaking vacuum in the RH furnace.
[0017] Furthermore, rare earth cerium is added in the form of ferrocerium alloy, and the rare earth element content in the ferrocerium alloy is 30%.
[0018] Furthermore, in step S3, when rare earth cerium treatment is performed, the contents of Ce, Alt, and S in the steel have the following relationship:
[0019] When total oxygen TO≤5ppm and S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0020] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] );
[0021] When total oxygen TO≤5ppm and 55ppm<S≤500ppm in steel, the relationship between Ce, Alt and S in steel is as follows:
[0022] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [1.0034×lg(S%)+0.508 );
[0023] When 5ppm<TO≤10ppm, S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0024] max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] );
[0025] When 5ppm<TO≤10ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0026] max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},1.2×10 [1.0034×lg(S%)+0.508] );
[0027] When 10ppm<TO≤20ppm, S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0028] max(-10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] );
[0029] When 10ppm<TO≤20ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0030] max(-10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [1.0034×lg(S%)+0.508] );
[0031] When 20ppm<TO≤50ppm and sulfur S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0032] max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] );
[0033] When 20ppm<TO≤50ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0034] max(-10 -3 ×{1.521×[lg(Alt%)-2] 2+8.155×[lg(Alt%)-2]-3.0155},10 [1.0034 ×lg(S%)+0 . 508] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] );
[0035] When 50ppm<TO≤100ppm and sulfur S≤55ppm in steel, the relationship between Ce, Alt and S in steel is as follows:
[0036] max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] );
[0037] When 50ppm<TO≤100ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0038] max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034×lg(S%)+0.508] )Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] ).
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) Since rare earth Ce has a high boiling point, it will not volatilize. The yield of rare earth Ce in the steel of the present invention is above 30-50%, which is much higher than the yield of calcium of 5-15%.
[0041] (2) By using the method of the present invention, the rare earth Ce treatment makes the sphericity of inclusions in the steel reach above 90%, thereby reducing the deterioration of steel properties caused by long strip-shaped MnS inclusions and non-deformable Al2O3 inclusions.
[0042] (3) Through the corrosion resistance test, it was found that the corrosion resistance of steel treated with rare earth Ce by the method of the present invention was reduced by more than 10% compared with the relative corrosion rate of calcium-treated steel.
[0043] (4) The technical solution of the present invention has opened up new avenues for the application of rare earth in steel, and provided a model for the modification of inclusions in steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The Ce-Al-O-Fe equilibrium phase diagram in steel at 1873K;
[0045] Figure 2 This is the Ce-Mn-SO-Fe equilibrium phase diagram in steel at 1273K. DETAILED DESCRIPTION
[0046] The following describes in further detail a method for treating inclusions in modified steel using rare earth cerium during refining, with reference to specific examples. These examples are for illustrative purposes only and the present invention is not limited thereto. It should be noted that all component contents in this specification are expressed in percentages by mass.
[0047] Recent studies have found that rare earth elements also have the ability to modify Al2O3 and MnS. The rare earth element Ce has similar properties to Ca and is highly reactive. Ce also has a higher boiling point and is less volatile during the smelting process, resulting in a higher yield than Ca. Therefore, using Ce, which has similar properties to Ca, to replace Ca for modification of some stable inclusions is highly suitable, indicating that the use of rare earth Ce in refining has significant application value.
[0048] The present invention provides a method for treating inclusions in modified steel using rare earth cerium during refining, comprising the following steps:
[0049] Step S1, converter or electric furnace smelting;
[0050] Step S2: When tapping steel from the converter or electric furnace, aluminum deoxidation and alloying operations are performed in the ladle;
[0051] Step S3, LF furnace or LF furnace → RH furnace refining, rare earth cerium treatment is performed in the last step of refining;
[0052] Step S4: continuous casting or die casting after refining.
[0053] Specifically, in step S1, the steel type smelted is the steel type that usually needs to be calcium treated during refining, such as pipeline steel, titanium-containing stainless steel, gear steel, heavy rail steel, electrical steel, non-quenched and tempered steel, deep drawing steel, structural steel, corrosion-resistant steel, wear-resistant steel, 10# high-quality carbon steel and other steel types.
[0054] Specifically, in step 2, aluminum deoxidation operation is performed using aluminum blocks or aluminum particles, the purity of the aluminum blocks or aluminum particles reaches more than 99%, and the equivalent diameter is no more than 12 mm.
[0055] In step S3, rare earth Ce treatment is performed in the last step of refining, that is, when only LF furnace refining is performed, rare earth treatment is performed before the LF furnace leaves the station; when refining from LF furnace to RH furnace, rare earth treatment is performed in the RH furnace.
[0056] Specifically, when only LF furnace refining is used, white slag is operated during refining, the slag thickness is controlled to be 130-150 mm, the white slag duration is greater than 20 minutes, argon is soft-blown before leaving the station, and rare earth cerium is added 4 minutes before leaving the station; the composition of the ladle top slag in LF furnace refining is calculated in percentage by mass as CaO: 55-65%, SiO2: 5-8%, MgO: 11-15%, Al2O3: 15-24%, FeO+MnO < 0.5%, CaO / SiO2: 8.0-11, and high basicity top slag is used to ensure that the recovery rate of rare earth elements is above 30%.
[0057] During refining from the LF furnace to the RH furnace, white slag is controlled during LF refining, with slag thickness controlled at 130-150mm and a white slag duration greater than 20 minutes. Argon is then soft-purged before leaving the furnace. The white slag composition, by mass, is CaO: 55-65%, SiO2: 5-8%, MgO: 11-15%, Al2O3: 15-24%, FeO+MnO < 0.5%, and CaO / SiO2: 8.0-11. After leaving the furnace, the LF furnace undergoes vacuum circulation degassing in the RH furnace. Rare earth cerium is added 4 minutes before breaking vacuum in the RH furnace. Argon is then soft-purged after breaking vacuum. High-basicity top slag is used to ensure a rare earth element yield of over 30%.
[0058] Specifically, before rare earth cerium treatment, the mass percentage of Alt in the steel is controlled to be 0.02%≤Alt<1.00%, the mass percentage of total oxygen TO is below 0.01%, and the mass percentage of sulfur S in the steel is below 0.05%; rare earth cerium is added in the form of ferrocerium alloy, and the rare earth element content in the ferrocerium alloy is 30%.
[0059] Specifically, when rare earth cerium treatment is performed, the contents of Ce, Alt and S in steel have the following relationship:
[0060] When total oxygen TO≤5ppm and S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0061] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ) (1)
[0062] When total oxygen TO≤5ppm and 55ppm<S≤500ppm in steel, the relationship between Ce, Alt and S in steel is as follows:
[0063] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [1.0034×lg(S%)+0.508] ) (2)
[0064] When 5ppm<TO≤10ppm, S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0065] max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ) (3)
[0066] When 5ppm<TO≤10ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0067] max(-10 -3 ×{1.08×[lg(Alt%)-2] 2+5.065×[lg(Alt%)-2]+3.39},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},1.2×10 [1.0034×lg(S%)+0.508] ) (4)
[0068] When 10ppm<TO≤20ppm, S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0069] max(-10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ) (5)
[0070] When 10ppm<TO≤20ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0071] max(-10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [1.0034×lg(S%)+0.508] ) (6)
[0072] When 20ppm<TO≤50ppm and sulfur S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0073] max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ) (7)
[0074] When 20ppm<TO≤50ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0075] max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] ) (8)
[0076] When 50ppm<TO≤100ppm and sulfur S≤55ppm in steel, the relationship between Ce, Alt and S in steel is as follows:
[0077] max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ) (9)
[0078] When 50ppm<TO≤100ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows:
[0079] max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034
[0080] ×lg(S%)+0.508] )<Ce%≤max(-2.4×10 -3×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] )(10)
[0081] It should be noted that the Ce%, Alt% and S% in the above formulas for steel are the values before the percentage sign %, that is, if Ce = 0.02%, then Ce% = 0.02; if Alt = 0.05%, then Alt% = 0.05; if S = 500ppm = 0.05%, then S% = 0.05.
[0082] Figure 1 The Ce-Al-O-Fe equilibrium phase diagram in steel at 1873K is shown in Figure 2. Figure 1 As can be seen, the following chemical reactions occur:
[0083] 1 / 3Ce+1 / 3Al+[O]=1 / 3CeAlO3 (11)
[0084] 2 / 3Al+[O]=1 / 3Al2O3 (12)
[0085] 1 / 3Ce+1 / 3Al2O3=1 / 3CeAlO3+1 / 3Al (13) Adding equation (11) to equation (13) yields the following equation:
[0086] 2 / 3Ce+[O]+1 / 3Al2O3=2 / 3CeAlO3 (14)
[0087] from Figure 1 As can be seen in the figure, there are iso-oxygen lines with TO = 5ppm, 10ppm, 20ppm, and 50ppm. The iso-oxygen lines represent the total oxygen content and the equilibrium line of the chemical reaction of formula (14) at 1873K. The point values on the iso-oxygen lines represent the critical contents of Ce and Alt corresponding to the equilibrium of the chemical reaction. The lower right range surrounded by each iso-oxygen line indicates that the chemical reaction of formula (14) has a tendency to proceed spontaneously from right to left. The amount of Al2O3 gradually increases as the reaction proceeds, and as the Ce content decreases and / or the Alt content increases, this tendency to proceed from right to left increases. On the contrary, outside this range, the chemical reaction represented by formula (14) tends to proceed spontaneously from left to right, and the amount of Al2O3 gradually decreases as the reaction proceeds. Moreover, as the Ce content increases and / or the Alt content decreases, this tendency of spontaneous reaction from left to right becomes increasingly stronger. The technical effect pursued by the modified inclusions of the present invention is to minimize the amount of Al2O3 generated in the steel. Therefore, under a certain Alt content, controlling the Ce content in the steel to not be lower than the critical content at the reaction equilibrium is the inherent meaning of the present invention.
[0088] The present invention is achieved by fitting Figure 1 The equilibrium lines of the chemical reaction of formula (14) under different isoxic lines are obtained to obtain the formula for the critical content of Ce. The obtained critical content of Ce is used as the lower limit of the Ce content in steel, and 1.2 times of the obtained critical content of Ce is used as the upper limit of the Ce content in steel.
[0089] Specifically, when the total oxygen TO in steel is less than or equal to 5ppm, the relationship between Ce and Alt in steel is as follows: -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4}<Ce%≤-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4}(15)
[0090] When 5ppm<TO≤10ppm in steel, the relationship between Ce and Alt in steel is as follows:
[0091] -10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39}<Ce%≤-1.2×10 -3
[0092] ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39}(16)
[0093] When 10ppm<TO≤20ppm in steel, the relationship between Ce and Alt in steel is as follows:
[0094] -10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1}<Ce%≤-1.2×10 -3 ×{1.9
[0095] ×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1}(17)
[0096] When 20ppm<TO≤50ppm in steel, the relationship between Ce and Alt in steel is as follows:
[0097] -10 -3 ×{1.521×[lg(Alt%)-2]2 +8.155×[lg(Alt%)-2]-3.0155}<Ce%≤-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155}(18)
[0098] It should be noted that the control level of total oxygen TO in the current steelmaking process is generally within 50ppm, and Figure 1 As can be seen from the figure, with the increase of the total oxygen TO content, the critical Ce content corresponding to the chemical reaction equilibrium of formula (14) at different Alt contents in the steel gradually approaches a similar value. That is, with the increase of the total oxygen TO content, the chemical reaction equilibrium is less and less affected by the change of the Alt content, but depends on a certain critical value of the Ce content. When TO = 50ppm, this phenomenon gradually becomes obvious, and the Ce content converges to 120.2~138ppm. Therefore, when TO in steel is greater than 50ppm and reaches 100ppm, the Ce content will inevitably converge further. In addition, it can be seen from formula (14) that when the Alt content is within a certain range and the total oxygen TO content is high enough, the balance of the chemical reaction in formula (14) depends more on the proportional relationship between the Ce content and the total oxygen TO content. Therefore, when TO increases from 50 ppm to 100 ppm, if the same reaction balance as when TO = 50 ppm is to be maintained, according to the proportional principle of chemical reaction, the critical Ce content must at least increase by 1 times the critical value corresponding to TO = 50 ppm. Therefore, when 50 ppm < TO ≤ 100 ppm in steel, the relationship between Ce and Alt in steel is as follows:
[0099] -2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155}<Ce%≤-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155}(19)
[0100] Similarly, another technical effect pursued by the modified inclusions of the present invention is to reduce the formation of MnS. Since MnS in steel is more likely to precipitate in steel below 1873K, but the precipitation temperature of MnS is higher than 1273K, it is necessary to establish a Ce-Mn-SO-Fe equilibrium phase diagram in steel at 1273K as a research object. Figure 2 The equilibrium phase diagram of Ce-Mn-SO-Fe in steel at 1273K is shown in Figure 2. Figure 2It can be seen that when S≤55ppm, the following chemical reactions will occur:
[0101] Mn+S=MnS (20)
[0102] Ce+[O]+MnS=1 / 2Ce2O2S+Mn+1 / 2S (21)
[0103] Figure 2 The vertical line in the lower right corner is the equilibrium line of the chemical reaction of formula (21). The point values on the equilibrium line represent the critical contents of Ce and S corresponding to the chemical reaction equilibrium. The right area of the equilibrium line indicates that the chemical reaction of formula (21) has a tendency to proceed spontaneously from right to left, and the amount of MnS gradually increases as the reaction proceeds. Moreover, as the Ce content decreases and / or the S content increases, this tendency of spontaneous reaction from right to left becomes increasingly stronger. The left area of the equilibrium line indicates that the chemical reaction of formula (21) has a tendency to proceed spontaneously from left to right, and the amount of MnS gradually decreases as the reaction proceeds. Moreover, as the Ce content increases and / or the S content decreases, this tendency of spontaneous reaction from left to right becomes increasingly stronger. The technical effect pursued by the modified inclusions of the present invention is to minimize the amount of MnS generated in steel. Therefore, under a certain S content, controlling the Ce content in steel to be not lower than the critical content at the reaction equilibrium is the inherent meaning of the present invention.
[0104] The present invention is achieved by fitting Figure 2 The equilibrium line of the chemical reaction in formula (21) is used to obtain the critical content formula of Ce. The obtained critical content of Ce is used as the lower limit of Ce content control in steel, and 1.2 times the obtained critical content of Ce is used as the upper limit of Ce content control in steel. Specifically, when S in steel is ≤55ppm, the relationship between Ce and S in steel is as follows:
[0105] 10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] <Ce%≤1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] (twenty two)
[0106] from Figure 2 It can be seen that when 55ppm<S≤500ppm, the following chemical reactions will occur:
[0107] Mn+S=MnS (20)
[0108] 3S+2Ce=Ce2S3 (23)
[0109] (x-2)Ce+Ce2S3+zMnS=Ce x S y +zMn+(z+3-y)S (24)
[0110] Figure 2The oblique line in the upper right corner is the equilibrium line of the chemical reaction of formula (24). The point values on the equilibrium line represent the critical contents of Ce and S corresponding to the chemical reaction equilibrium. The right area of the equilibrium line indicates that the chemical reaction of formula (24) has a tendency to proceed spontaneously from right to left, and the amount of MnS gradually increases as the reaction proceeds. Moreover, as the Ce content decreases and / or the S content increases, this tendency of spontaneous reaction from right to left becomes increasingly stronger. The left area of the equilibrium line indicates that the chemical reaction of formula (24) has a tendency to proceed spontaneously from left to right, and the amount of MnS gradually decreases as the reaction proceeds. Moreover, as the Ce content increases and / or the S content decreases, this tendency of spontaneous reaction from left to right becomes increasingly stronger. The technical effect pursued by the modified inclusions of the present invention is to minimize the amount of MnS generated in steel. Therefore, under a certain S content, controlling the Ce content in steel to be not lower than the critical content at the reaction equilibrium is the inherent meaning of the present invention.
[0111] The present invention is achieved by fitting Figure 2 The equilibrium line of the chemical reaction in formula (24) is used to obtain the critical content formula of Ce. The obtained critical content of Ce is used as the lower limit of Ce content control in steel, and 1.2 times the obtained critical content of Ce is used as the upper limit of Ce content control in steel. Specifically, when 55ppm<S≤500ppm in steel, the relationship between Ce and S in steel is as follows:
[0112] 10 [1.0034×lg(S%)+0.508] <Ce%≤1.2×10 [1.0034×lg(S%)+0.508] (25)
[0113] Since the generation of Al2O3 and MnS needs to be limited simultaneously in the present invention, the five regions with different total oxygen TO contents, i.e., equations (15) to (19), and the two regions with different S contents, i.e., equations (22) and (25), are combined to obtain the corresponding 10 Ce relationship equations, i.e., equations (1) to (10).
[0114] When the Ce% calculated using formulas (1) to (10) is less than 0, it is considered zero. The Ce content determined by the above formula is the Ce content present in the steel. When adding ferrocerium alloy during refining, the amount of ferrocerium alloy added must be calculated based on the rare earth yield in the steel and the cerium content in the ferrocerium alloy. In the present invention, the rare earth yield is calculated as a minimum of 30%, and the cerium content in the ferrocerium alloy is 30%. Therefore, the amount of ferrocerium alloy added in the present invention is Ce / 0.09.
[0115] Comparative Example
[0116] Step S1, smelting pipeline steel X80 in a converter;
[0117] Step S2: When the converter is tapping, aluminum deoxidation and alloying operations are performed in the ladle, and the mass of the molten steel is 260t;
[0118] Step S3, LF furnace → RH furnace refining;
[0119] S1: LF refining in place temperature is 1562 ℃, white slag is made for deoxidation and desulfurization, the S content of molten steel is controlled to be less than 0.0020%, the Alt content is within the range of 0.03-0.04%, the TO content of molten steel is less than 10ppm, and the temperature is adjusted. The white slag duration is 22 minutes. The white slag composition is CaO: 55.45%, SiO2: 11.57%, Al2O3: 27.34%, MgO: 5.06%, TFeO: 0.35%, MnO: 0.22%, the basicity CaO / SiO2 is 4.8, and the slag thickness is 116mm. The soft argon blowing time is 6 minutes, and the soft argon blowing volume is 0.008Nm 3 / (t·min), LF departure temperature is 1594℃.
[0120] S2: After the LF furnace is refined, it is transferred to the RH furnace. The RH refining temperature is 1585℃. The vacuum cycle degassing is carried out in the RH furnace with a vacuum degree of 160Pa and a holding time of 18 minutes. During the vacuum degassing, the Alt content is controlled at 0.03%. After breaking the vacuum, 23.2kg of calcium wire is fed. After feeding the calcium wire, the [Ca] content in the molten steel is controlled within the range of 0.0005-0.0022%. After measurement, it is 0.0008%. The soft blowing time of argon is 10 minutes, and the soft blowing amount of argon is 0.007Nm 3 / (t·min), RH departure temperature 1562℃.
[0121] Table 1 Chemical composition (wt%) of RH off-station in comparative examples of the present invention
[0122] Test number C Si Mn P S Als Ca Cr Ni Cu Comparative Example 0.09 0.42 1.85 0.022 0.005 0.035 0.0008 0.45 0.30 0.25
[0123] The calcium recovery rate was calculated to be 8.9%.
[0124] Step S4: continuous casting after refining.
[0125] Testing revealed that the inclusions in the finished product were CaS and 12CaO·7Al2O3, with spherical inclusions accounting for 87.5%. Some Al2O3 inclusions were also present.
[0126] Example 1
[0127] Step S1, smelting corrosion-resistant steel Q450NQR1 in a converter;
[0128] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99%, the maximum equivalent diameter is 9 mm, and the mass of the molten steel is 260 tons.
[0129] Step S3, LF furnace → RH furnace refining;
[0130] S1: LF refining in-situ temperature is 1563℃, white slag operation is carried out in LF furnace refining, slag thickness is controlled to be 132mm, white slag duration is 22min, white slag composition is calculated by mass percentage as CaO: 55%, SiO2: 6%, MgO: 15%, Al2O3: 23.6%, FeO+MnO: 0.4%, CaO / SiO2: 9.1, argon is soft-blown before leaving the station, soft argon blowing time is 6min, soft argon blowing volume is 0.008Nm 3 / (t·min), LF departure temperature is 1592℃.
[0131] S2: After the LF furnace is refined, it is transported to the RH furnace. The RH refining temperature is 1589℃. The vacuum cycle degassing is carried out in the RH1 furnace. The vacuum degree is 160Pa and the holding time is 18min. 4min before breaking the vacuum, 4.3kg of ferrocerium alloy is added. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.05%, the mass percentage of total oxygen TO is 5ppm, and the mass percentage of sulfur S in the steel is 0.0030%. After breaking the vacuum, argon is soft-blown for 10min and the soft-blowing amount is 0.007Nm 3 / (t·min), RH departure temperature 1565℃.
[0132] The amount of ferrocerium alloy added is calculated according to the following steps:
[0133] (1) Calculate the Ce content to be retained in the steel
[0134] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ),have to:
[0135] max(1.24×10 -4 , 2.6×10 -6 )<Ce%≤max(1.49×10 -4 , 3.12×10 -6 ), take the upper limit Ce% = 1.49 × 10 -4 ;
[0136] (2) Calculate the amount of ferrocerium alloy added
[0137] The Ce recovery rate is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%. (260t×1.49×10 -4 % / 0.09) / (1-1.49×10 -4 % / 0.09)=4.3kg.
[0138] Table 2 Chemical composition (wt%) of the RH off-station in Example 1 of the present invention
[0139] Test number C Si Mn P S Als Cr Ni Cu Ce 1 0.05 0.08 1.30 0.011 0.003 0.05 0.73 0.30 0.38 0.00015
[0140] The actual yield of Ce was calculated to be 30.2%.
[0141] Step S4: continuous casting after refining.
[0142] After testing, it was found that the main types of inclusions in the finished product were CeAlO3, with spherical inclusions accounting for more than 92.1%, and no MnS and Al2O3 inclusions.
[0143] Example 2
[0144] Step S1, smelting wear-resistant steel NM400 in a converter;
[0145] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99.2%, the maximum equivalent diameter is 12 mm, and the mass of the molten steel is 260 t.
[0146] Step S3, LF furnace refining;
[0147] The LF refining in-situ temperature is 1565℃, and white slag operation is performed during LF furnace refining. The slag thickness is controlled to be 139mm, the white slag duration is 22min, and the white slag composition is calculated in mass percentage as CaO: 65%, SiO2: 5.91%, MgO: 11%, Al2O3: 17.6%, FeO+MnO: 0.49%, CaO / SiO2: 11. 860.8kg of ferrocerium alloy is added 4min before leaving the station. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.02%, the mass percentage of total oxygen TO is 80ppm, and the mass percentage of sulfur S in the steel is 80ppm. Argon is soft-blown before leaving the station, the soft-blowing time is 6min, the soft-blowing amount of argon is 0.008Nm3 / (t·min), and the LF leaving station temperature is 1592℃.
[0148] The amount of ferrocerium alloy added is calculated according to the following steps:
[0149] (1) Calculate the Ce content to be retained in the steel
[0150] max(-2×10-3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034×lg(S%)+0.508] )<Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] ), we get:
[0151] max(0.0247, 0.0253)<Ce%≤max(0.0296, 0.0304), take Ce%=0.03;
[0152] (2) Calculate the amount of ferrocerium alloy added
[0153] The Ce yield is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.03% / 0.09] / (1-0.03% / 0.09)=860.8kg
[0154] Table 2 Chemical composition (wt%) of LF off-station in Example 1 of the present invention
[0155] Test number C Si Mn P S Als Cr Ni Cu Ce 1 0.30 0.70 1.60 0.025 0.0080 0.05 0.70 0.30 0.25 0.0301
[0156] The actual yield of cerium was calculated to be 30%.
[0157] Step S4: continuous casting after refining.
[0158] Testing revealed that the inclusions in the finished product were Ce2O2S, with spherical inclusions accounting for over 98%. There were no MnS or Al2O3 inclusions.
[0159] Example 3
[0160] Step S1, smelting 10# high-quality carbon steel in a converter;
[0161] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99.5%, the maximum equivalent diameter is 10 mm, and the mass of the molten steel is 260 tons.
[0162] Step S3, LF furnace refining;
[0163] The LF refining temperature is 1563℃, and the white slag operation in the LF furnace refining is carried out. The slag thickness is controlled to be 140mm, the white slag duration is 21min, and the white slag composition is calculated as CaO: 55%, SiO2: 5.6%, MgO: 15%, Al2O3: 24%, FeO+MnO: 0.4%, CaO / SiO2: 9.82 in mass percentage. 710kg of ferrocerium alloy is added 4min before leaving the station. Before adding ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.05%, the mass percentage of total oxygen TO is 8ppm, and the mass percentage of sulfur S in the steel is 75ppm. Argon is soft-blown before leaving the station, the soft-blowing time is 10min, and the soft-blowing amount of argon is 0.007Nm 3 / (t·min), LF departure temperature is 1598℃.
[0164] The amount of ferrocerium alloy added is calculated according to the following steps:
[0165] (1) Calculate the Ce content to be retained in the steel
[0166] max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},1.2×10 [1.0034×lg(S%)+0.508] ), we get:
[0167] max(0.00156, 0.0238)<Ce%≤max(0.0019, 0.0286), take Ce%=0.0245;
[0168] (2) Calculate the amount of ferrocerium alloy added
[0169] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.0245% / 0.09] / (1-0.0245% / 0.09)=710kg.
[0170] Table 4 Chemical composition (wt%) of LF off-station in Example 3 of the present invention
[0171] Test number C Si Mn P S Als Cr Ni Cu Ce 3 0.076 0.21 0.496 0.008 0.0075 0.05 0.15 0.20 0.25 0.0254
[0172] The actual yield of cerium was calculated to be 31.1%.
[0173] Step S4: continuous casting after refining.
[0174] After testing, the type of inclusions in the finished product is Ce2O2S, spherical inclusions account for more than 95%, and there are no MnS and Al2O3 inclusions.
[0175] Example 4
[0176] Step S1, smelting gear steel 20CrMnTi in a converter;
[0177] Step S2: When the converter is tapping, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99%, the maximum equivalent diameter is 11 mm, and the mass of the molten steel is 260 tons.
[0178] Step S3, LF furnace refining;
[0179] The LF refining temperature is 1567℃, and the white slag operation is carried out in the LF furnace refining. The slag thickness is controlled to be 140mm, the white slag duration is 23min, and the white slag composition is calculated as CaO: 62.7%, SiO2: 7%, MgO: 15%, Al2O3: 15%, FeO+MnO: 0.3%, CaO / SiO2: 8.96 in mass percentage. 127kg of ferrocerium alloy is added 4min before leaving the station. Before adding ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.03%, the mass percentage of total oxygen TO is 20ppm, and the mass percentage of sulfur S in the steel is 20ppm. Argon is soft-blown before leaving the station, the soft-blowing time is 10min, and the soft-blowing amount of argon is 0.007Nm 3 / (t·min), LF departure temperature is 1587℃.
[0180] The amount of ferrocerium alloy added is calculated according to the following steps:
[0181] (1) Calculate the Ce content to be retained in the steel
[0182] max(-10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ); calculated: max(0.0040, 0.0000)<Ce%≤max(0.0048, 0.0000), take Ce%=0.0044;
[0183] (2) Calculate the amount of ferrocerium alloy added
[0184] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.0044% / 0.09] / (1-0.0044% / 0.09)=127kg.
[0185] Table 5 Chemical composition (wt%) of LF off-station in Example 4 of the present invention
[0186] Test number C Si Mn P S Als Cr Ti Ni Ce 4 0.21 0.25 0.90 0.02 0.002 0.03 1.1 0.08 0.20 0.0046
[0187] The actual yield of cerium was calculated to be 31.6%.
[0188] Step S4: continuous casting after refining.
[0189] After testing, the type of inclusions in the finished product is CeAlO3, spherical inclusions account for more than 96%, and there are no MnS and Al2O3 inclusions.
[0190] Example 5
[0191] Step S1, smelting gear steel 20CrMnTi in a converter;
[0192] Step S2: When the converter is tapping, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99.1%, the maximum equivalent diameter is 9 mm, and the mass of the molten steel is 260 tons.
[0193] Step S3, LF furnace refining → RH furnace refining;
[0194] S1: LF refining in-place temperature is 1561°C. During LF refining, white slag is operated, with a slag thickness of 150 mm and a white slag duration of 23 minutes. Argon is soft-purged before leaving the station. The white slag composition, by mass percentage, is CaO: 58.15%, SiO2: 6.5%, MgO: 13%, Al2O3: 22%, FeO + MnO = 0.35%, and CaO / SiO2: 8.94. The LF exit temperature is 1590°C.
[0195] S2: After the LF furnace is refined, it is transferred to the RH furnace. The RH refining temperature is 1585℃. The RH furnace is vacuum cycled and degassed with a vacuum degree of 160Pa for 18min. 870kg of ferrocerium alloy is added 4min before the vacuum is broken in the RH furnace. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is 0.06%, the mass percentage of total oxygen TO is 60ppm, and the mass percentage of sulfur S in the steel is 10ppm. Argon is soft-blown before leaving the station for 10min with a soft-blowing volume of 0.007Nm 3 / (t·min), RH departure temperature 1569℃.
[0196] The amount of ferrocerium alloy added is calculated according to the following steps:
[0197] (1) Calculate the Ce content to be retained in the steel
[0198] max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ), calculated as follows: max(0.027, 0.0000)<Ce%≤max(0.0324, 0.0000), take Ce%=0.030;
[0199] (2) Calculate the amount of ferrocerium alloy added
[0200] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.030% / 0.09] / (1-0.030% / 0.09)=870kg.
[0201] Table 6 Chemical composition (wt%) of LF off-station in Example 5 of the present invention
[0202] Test number C Si Mn P S Als Cr Ni Ti Ce 5 0.19 0.30 0.97 0.009 0.001 0.06 1.2 0.19 0.07 0.0314
[0203] The actual yield of cerium was calculated to be 31.4%.
[0204] Step S4: continuous casting after refining.
[0205] After testing, the type of inclusions in the finished product is CeAlO3, spherical inclusions account for more than 93%, and there are no MnS and Al2O3 inclusions.
[0206] Example 6
[0207] Step S1, smelting heavy rail steel U75 in a converter;
[0208] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99.8%, the maximum equivalent diameter is 11.5 mm, and the mass of the molten steel is 260 tons.
[0209] Step S3, LF furnace refining → RH furnace refining;
[0210] S1: LF refining in-place temperature 1554°C. White slag operation during LF refining, slag thickness controlled at 130 mm, white slag duration 23 minutes, and argon soft purge before leaving the station. White slag composition, by mass percentage, is CaO: 56%, SiO2: 7%, MgO: 13.8%, Al2O3: 23%, FeO + MnO = 0.2%, CaO / SiO2: 8. LF exit temperature 1597°C.
[0211] S2: After the LF furnace is refined, it is transferred to the RH furnace. The RH refining temperature is 1588℃. The RH furnace is vacuum cycled and degassed with a vacuum degree of 160Pa for 18 minutes. 957kg of ferrocerium alloy is added 4 minutes before the vacuum is broken in the RH furnace. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is 0.02%, the mass percentage of total oxygen TO is 30ppm, and the mass percentage of sulfur S in the steel is 100ppm. Argon is soft-blown before leaving the station for 10 minutes with a soft-blowing amount of 0.007Nm 3 / (t·min), RH departure temperature 1565℃.
[0212] The amount of ferrocerium alloy added is calculated according to the following steps:
[0213] (1) Calculate the Ce content to be retained in the steel
[0214] max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034 ×lg(S%)+0 . 508] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] ), we get:
[0215] max(0.0124, 0.0317)<Ce%≤max(0.0149, 0.0381), take Ce%=0.0330;
[0216] (2) Calculate the amount of ferrocerium alloy added
[0217] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.033% / 0.09] / (1-0.033% / 0.09)=957kg.
[0218] Table 7 Chemical composition (wt%) of LF off-station in Example 6 of the present invention
[0219] Test number C Si Mn P S Als Ce 6 0.75 0.55 0.79 0.014 0.01 0.02 0.0330
[0220] The actual yield of cerium was calculated to be 30.0%.
[0221] Step S4: continuous casting after refining.
[0222] After testing, the type of inclusions in the finished product is Ce2O2S, with spherical inclusions accounting for more than 97%, and no MnS and Al2O3 inclusions.
[0223] Example 7
[0224] Step S1, smelting heavy rail steel U75 in a converter;
[0225] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99%, the maximum equivalent diameter is 10 mm, and the mass of the molten steel is 260 tons.
[0226] Step S3, LF furnace refining;
[0227] The LF refining temperature is 1563℃, and the white slag operation is carried out in the LF furnace refining. The slag thickness is controlled to be 140mm, the white slag duration is 23min, and the white slag composition is calculated as CaO: 64%, SiO2: 6.4%, MgO: 13%, Al2O3: 16.3%, FeO+MnO: 0.3%, CaO / SiO2: 10 in mass percentage. 4min before leaving the station, 69kg ferrocerium alloy is added. Before adding ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.05%, the mass percentage of total oxygen TO is 8ppm, and the mass percentage of sulfur S in the steel is 10ppm. Soft argon is blown before leaving the station, the soft argon blowing time is 10min, and the soft argon blowing volume is 0.007Nm 3 / (t·min), LF departure temperature is 1587℃.
[0228] The amount of ferrocerium alloy added is calculated according to the following steps:
[0229] (1) Calculate the Ce content to be retained in the steel
[0230] max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2+5.065×[lg(Alt%)-2]+3.39},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ), we get:
[0231] max(0.0016, 0.0000)<Ce%≤max(0.0032, 0.0000), take Ce%=0.0024;
[0232] (2) Calculate the amount of ferrocerium alloy added
[0233] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.0024% / 0.09] / (1-0.0024% / 0.09)=69kg.
[0234] Table 8 Chemical composition (wt%) of LF off-station in Example 7 of the present invention
[0235] Test number C Si Mn P S Als Ce 7 0.76 0.70 0.92 0.019 0.001 0.05 0.0026
[0236] The actual yield of cerium was calculated to be 32.2%.
[0237] Step S4: refining and then die casting.
[0238] After testing, the type of inclusions in the finished product is CeAlO3, spherical inclusions account for more than 96%, and there are no MnS and Al2O3 inclusions.
[0239] Example 8
[0240] Step S1, smelting Q355 structural steel in a converter;
[0241] Step S2: When the converter is tapping, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99.9%, the maximum equivalent diameter is 9 mm, and the mass of the molten steel is 260 tons.
[0242] Step S3, LF furnace refining → RH furnace refining;
[0243] S1: LF refining in-place temperature is 1564°C. During LF refining, white slag is operated, slag thickness is controlled at 145mm, white slag duration is 23 minutes, and argon is soft-purged before leaving the furnace. The white slag composition, by mass percentage, is CaO: 58%, SiO2: 6%, MgO: 12%, Al2O3: 23.6%, FeO + MnO = 0.4%, and CaO / SiO2: 9.7. The LF exit temperature is 1599°C.
[0244] S2: After the LF furnace is refined, it is transferred to the RH furnace. The RH refining temperature is 1589℃. The RH furnace is vacuum cycled and degassed with a vacuum degree of 160Pa for 18min. 1015kg of ferrocerium alloy is added 4min before the vacuum is broken in the RH furnace. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is 0.04%, the mass percentage of total oxygen TO is 4ppm, and the mass percentage of sulfur S in the steel is 100ppm. Argon is soft-blown before leaving the station for 10min and the amount of argon is 0.007Nm 3 / (t·min), RH departure temperature 1568℃.
[0245] The amount of ferrocerium alloy added is calculated according to the following steps:
[0246] (1) Calculate the Ce content to be retained in the steel
[0247] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [1.0034×lg(S%)+0.508] ), we get:
[0248] max(0.0000, 0.0317)<Ce%≤max(0.0000, 0.038), take Ce%=0.035;
[0249] (2) Calculate the amount of ferrocerium alloy added
[0250] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.035% / 0.09] / (1-0.035% / 0.09)=1015kg.
[0251] Table 9 Chemical composition (wt%) of LF off-station in Example 8 of the present invention
[0252] Test number C Si Mn P S Als Cr Ni Cu Ce 8 0.21 0.45 1.48 0.026 0.01 0.04 0.3 0.24 0.30 0.04
[0253] The actual yield of cerium was calculated to be 34.3%.
[0254] Step S4: continuous casting after refining.
[0255] After testing, the type of inclusions in the finished product is Ce2O2S, with spherical inclusions accounting for more than 93%, and no MnS and Al2O3 inclusions.
[0256] Example 9
[0257] Step S1, smelting Q355 structural steel in a converter;
[0258] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99.4%, the maximum equivalent diameter is 10 mm, and the mass of the molten steel is 260 tons.
[0259] Step S3, LF furnace refining;
[0260] The LF refining temperature is 1565℃, and white slag operation is performed during LF furnace refining. The slag thickness is controlled to be 135mm, the white slag duration is 23min, and the white slag composition is calculated as CaO: 58%, SiO2: 6.2%, MgO: 13.7%, Al2O3: 22%, FeO+MnO: 0.1%, CaO / SiO2: 9.4 in mass percentage. 2921kg of ferrocerium alloy is added 4min before leaving the station. Before adding ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.05%, the mass percentage of total oxygen TO is 15ppm, and the mass percentage of sulfur S in the steel is 300ppm. Argon is soft-blown before leaving the station, the soft-blowing time is 10min, and the soft-blowing amount of argon is 0.007Nm 3 / (t·min), LF departure temperature is 1589℃.
[0261] The amount of ferrocerium alloy added is calculated according to the following steps:
[0262] (1) Calculate the Ce content to be retained in the steel
[0263] max(-10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(Alt%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [1.0034×lg(S%)+0.508] ), we get:
[0264] max(0.0045, 0.0955)<Ce%≤max(0.0169, 0.1146), take Ce%=0.1;
[0265] (2) Calculate the amount of ferrocerium alloy added
[0266] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.1% / 0.09] / (1-0.1% / 0.09)=2921kg.
[0267] Table 10 Chemical composition (wt%) of LF off-station in Example 9 of the present invention
[0268] Test number C Si Mn P S Als Cr Ni Cu Ce 9 0.24 0.55 1.50 0.004 0.003 0.05 0.3 0.3 0.4 0.1
[0269] The actual yield of cerium was calculated to be 30%.
[0270] Step S4: continuous casting after refining.
[0271] After testing, the type of inclusions in the finished product is Ce2O2S, with spherical inclusions accounting for more than 93%, and no MnS and Al2O3 inclusions.
[0272] Example 10
[0273] Step S1, smelting Q450NQR1 in a converter;
[0274] Step S2: When the converter is tapping steel, aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99%, the maximum equivalent diameter is 9 mm, and the mass of the molten steel is 260 tons.
[0275] Step S3, LF furnace refining → RH furnace refining;
[0276] S1: LF refining in-place temperature 1561°C. White slag operation during LF refining, slag thickness controlled at 133mm, white slag duration 23 minutes, argon soft purge before leaving the furnace. White slag composition, by mass percentage, is CaO: 56%, SiO2: 7%, MgO: 13%, Al2O3: 23.52%, FeO + MnO = 0.48%, CaO / SiO2: 8. LF exit temperature 1590°C.
[0277] S2: After the LF furnace is refined, it is transferred to the RH furnace. The RH refining temperature is 1585℃. The RH1 furnace is vacuum cycled and degassed with a vacuum degree of 160Pa for 18 minutes. 579kg of ferrocerium alloy is added 4 minutes before the vacuum is broken in the RH furnace. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is 0.06%, the mass percentage of total oxygen TO is 30ppm, and the mass percentage of sulfur S in the steel is 55ppm. Argon is soft-blown before leaving the station for 10 minutes and the amount of soft-blown argon is 0.007Nm 3 / (t·min), RH departure temperature 1564℃.
[0278] The amount of ferrocerium alloy added is calculated according to the following steps:
[0279] (1) Calculate the Ce content to be retained in the steel
[0280] max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ), calculated as follows: max(0.0135, 0.0174)<Ce%≤max(0.0162, 0.0209), take Ce%=0.0200;
[0281] (2) Calculate the amount of ferrocerium alloy added
[0282] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, [260t×0.02% / 0.09] / (1-0.02% / 0.09)=579kg.
[0283] Table 11 Chemical composition (wt%) of LF off-station in Example 10 of the present invention
[0284] Test number C Si Mn P S Als Cr Ni Cu Ce 10 0.70 0.74 1.39 0.005 0.0055 0.06 1.0 0.5 0.30 0.0210
[0285] The actual yield of cerium was calculated to be 31.5%.
[0286] Step S4: continuous casting after refining.
[0287] After testing, the type of inclusions in the finished product is Ce2O2S, with spherical inclusions accounting for more than 93%, and no MnS and Al2O3 inclusions.
[0288] Example 11
[0289] Step S1, smelting high aluminum steel 38CrMoAl in an electric furnace;
[0290] Step S2: When the electric furnace is tapping steel, aluminum is added along with the steel flow, and aluminum deoxidation and alloying operations are performed in the ladle. The purity of the aluminum block is 99%, the maximum equivalent diameter is 9 mm, and the mass of the molten steel is 100 tons;
[0291] Step S3, LF furnace → RH furnace refining;
[0292] S1: LF refining in-situ temperature is 1563℃, white slag operation is carried out in LF furnace refining, slag thickness is controlled to be 132mm, white slag duration is 22min, white slag composition is calculated by mass percentage as CaO: 64%, SiO2: 8%, MgO: 12%, Al2O3: 15.6%, FeO+MnO: 0.4%, CaO / SiO2: 8, argon is soft-blown before leaving the station, soft argon blowing time is 6min, soft argon blowing volume is 0.008Nm 3 / (t·min), LF departure temperature is 1592℃.
[0293] S2: After the LF furnace is refined, it is transported to the RH furnace. The RH refining temperature is 1589℃. The vacuum cycle degassing is carried out in the RH1 furnace. The vacuum degree is 160Pa and the holding time is 18min. The vacuum degree is 160Pa and the holding time is 18min. 28.9kg of ferrocerium alloy is added 4min before breaking the vacuum. Before adding the ferrocerium alloy, the mass percentage of Alt in the steel is measured to be 0.95%, the mass percentage of total oxygen TO is 5ppm, and the mass percentage of sulfur S in the steel is 0.0030%. After breaking the vacuum, argon is soft-blown for 10min and the soft-blowing amount is 0.007Nm 3 / (t·min), RH departure temperature 1565℃.
[0294] The amount of ferrocerium alloy added is calculated according to the following steps:
[0295] (1) Calculate the Ce content to be retained in the steel
[0296] max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [1.0034×lg(S%)+0.508] ),have to:
[0297] max(9.7×10 -4 , 2.6×10 -6 )<Ce%≤max(1.16×10 -3 , 3.12×10 -6 ), take Ce% = 0.001;
[0298] (2) Calculate the amount of ferrocerium alloy added
[0299] The yield of Ce is calculated as 30%, and the cerium content in the ferrocerium alloy is calculated as 30%, (100t×0.001% / 0.09) / (1-0.001% / 0.09)=28.9kg.
[0300] Table 12 Chemical composition (wt%) of the RH off-station in Example 11 of the present invention
[0301] Test number C Si Mn P S Als Cr Mo Ce 11 0.40 0.30 0.50 0.011 0.003 0.95 1.5 0.20 0.001
[0302] The actual yield of Ce was calculated to be 30%.
[0303] Step S4: refining and then die casting.
[0304] After testing, it was found that the main types of inclusions in the finished product were CeAlO3, with spherical inclusions accounting for more than 91%, and no MnS and Al2O3 inclusions.
[0305] The steels of the ten embodiments were subjected to a cyclic immersion corrosion test using NaHSO 3 as the corrosive solution for 75 h. Compared with the calcium-treated steels of the same type, the relative corrosion rates of the embodiments were all below 90%.
Claims
1. A method for treating inclusions in modified steel using rare earth cerium during refining, characterized in that: The method comprises the following steps: Step S1, converter or electric furnace smelting; Step S2: When tapping steel from a converter or electric furnace, aluminum deoxidation and alloying operations are performed in a ladle; Step S3, LF furnace or LF furnace → RH furnace refining, rare earth cerium treatment is performed in the last step of refining; Step S4, continuous casting or die casting after refining; In step S3, before the rare earth cerium treatment, the mass percentage of Alt in the steel is controlled to be 0.02% ≤ Alt < 1.00%, the mass percentage of total oxygen TO is below 0.01%, and the mass percentage of sulfur S is below 0.05%; In step S3, when rare earth cerium treatment is performed, the contents of Ce, Alt and S in the steel have the following relationship: When total oxygen TO≤5ppm and S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ); When total oxygen TO≤5ppm and 55ppm<S≤500ppm in steel, the relationship between Ce, Alt and S in steel is as follows: max(-10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -4 ×{7.4×[lg(Alt%)-2] 2 +32.8×[lg(Alt%)-2]+26.4},1.2 ×10 [1.0034×lg(S%)+0.508 ); When 5ppm<TO≤10ppm, S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065 ×[lg(Alt%)-2]+3.39},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ); When 5ppm<TO≤10ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.08×[lg(Alt%)-2] 2 +5.065×[lg(Alt%)-2]+3.39},1.2×10 [1.0034×lg(S%)+0.508] ); When 10ppm<TO≤20ppm, S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -3 ×{1.9×[lg(All%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.9×[lg(All%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ); When 10ppm<TO≤20ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -3 ×{1.9×[lg(All%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},10 [1.0034×lg(S%)+0.508] )< Ce%≤max(-1.2×10 -3 ×{1.9×[lg(All%)-2] 2 +10.4×[lg(Alt%)-2]+9.1},1.2 ×10 [1.0034×lg(S%)+0.508] ); When 20ppm<TO≤50ppm and sulfur S≤55ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ); When 20ppm<TO≤50ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034 ×lg(S%)+0.508] )<Ce%≤max(-1.2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2] -3.0155},1.2×10 [1.0034×lg(S%)+0.508] ); When 50ppm<TO≤100ppm and sulfur S≤55ppm in steel, the relationship between Ce, Alt and S in steel is as follows: max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [-46.223 ×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] )<Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [-46.223×lg(S%)×lg(S%)-206.55×lg(S%)-232.474] ); When 50ppm<TO≤100ppm, 55ppm<S≤500ppm in steel, the relationship among Ce, Alt and S in steel is as follows: max(-2×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},10 [1.0034 ×lg(S%)+0.508] )Ce%≤max(-2.4×10 -3 ×{1.521×[lg(Alt%)-2] 2 +8.155×[lg(Alt%)-2]-3.0155},1.2×10 [1.0034×lg(S%)+0.508] ); In the above formula, Ce%, Alt% and S% in steel are expressed as the values before the percentage sign %.
2. The method according to claim 1, characterized in that In the step S2, the aluminum deoxidation is performed by using aluminum blocks or aluminum particles, the purity of the aluminum blocks or aluminum particles reaches more than 99%, and the equivalent diameter is not greater than 12 mm.
3. The method according to claim 1, characterized in that In step S3, during the white slag refining in the LF furnace, the slag thickness is controlled to be 130-150 mm, the white slag duration is greater than 20 minutes, and argon is soft-blown before leaving the station.
4. The method according to claim 3, characterized in that The white slag comprises, in mass percentage, CaO: 55-65%, SiO2: 5-8%, MgO: 11-15%, Al2O3: 15-24%, FeO+MnO<0.5%, and CaO / SiO2: 8.0-11.
5. The method according to claim 1, characterized in that: In step S3, the rare earth cerium treatment in the last step of refining is: when only LF furnace is used for refining, rare earth cerium is added 4 minutes before leaving the station; when refining from LF furnace to RH furnace, rare earth cerium is added 4 minutes before breaking vacuum in the RH furnace.
6. The method according to claim 5, characterized in that The rare earth cerium is added in the form of ferrocerium alloy, and the rare earth element content in the ferrocerium alloy is 30%.
Citation Information
Patent Citations
Rare earth-containing NM600 wear-resistant steel plate and preparation method thereof
CN114480987A
Rare earth-containing corrosion-resistant steel and method for controlling content and existence form of rare earth
CN114672728A
Corrosion-resistant steel with high rare earth cerium content and refining control method thereof
CN114672729A